Bio-Psychosocial Consequences of Aids on the quality of life of HIV Serum-Positive people - Castanha, Alessandra R; Coutinho, Maria da Penha L; Saldanha, Ana AW; Oliveira, Josevânia SC (Brazilian Journal of Sexually Transmitted Diseases, 2006)
Introduction: the increase of the survival of HIV serum-positive people lead to new sources of uncertainty caused by the renegotiation that these people needto do regarding their feelings of hope and orientation about the future, as well as their social role and identities, and their interpersonal relationships andquality of life (QL). Objective: to evaluate the bio-psychosocial consequences of aids on the quality of life of HIV serum-positive persons. Methods: twenty-six people of both genders look part in this study. The technique of semi-structured interview was used. The data was categorized by the content thematicanalysis of Bardin (2002). Results: two thematic classes arogefrom the emergent contents of the semi-structured interviews submitted to the contentthematic analysis of Bardin. The first – Aids, has one category – representations of aids and four sub-categories – disease, death, sorrow and naturalization–. The second thematic class – bio-psychosocialconsequences of aids on the QL was divided in to three categories: the first one was the physic-organic, withthree sub-categories – physiologic perturbations, physical capacity and side effects of the medication; the second one was psycho-affective, with foursubcategories – prejudice, depression, self-esteem and self-perception; and the last category was the behavioral, with two sub-categories – isolation andsexuality; Conclusion: the bio-psychosocial consequences found in this study demonstrated the influence of aids on the QL of HIV serum-positive people,highlighting their main origins, showing the importance of their analysis when it comes to the context of the QL.